Pengembangan Modul Pembelajaran Pengantin Paes Ageng Jangan Menir - Sri Irtawidjajanti; Lilis Jubaedah; Lintang Ayu Panjer Wengi; Zefanya Christy Gustanto (Departement of Mathematics Education, 2024)
Yogya Paes Ageng Jangan Menir Bridal make-up is a type of make-up that requires its own technique in the manufacturing process, so students must be careful and follow the stages in completing it. The aim of this research is to develop a suitable learning media module, equipped with a video of the stages in the form of a QR barcode, which can be practically used by students or learners, as an independent learning media. The stages of the process of using cosmetics are in accordance with the times and the